2015
DOI: 10.1093/jee/tov270
|View full text |Cite
|
Sign up to set email alerts
|

Larvicidal Effects of Four Citrus Peel Essential Oils Against the Arbovirus VectorAedes albopictus(Diptera: Culicidae)

Abstract: In this study, we evaluated the larvicidal activity of four citrus essential oils (EOs; sweet orange, mandarin, bergamot, and lemon) against the arbovirus vector Aedes albopictus (Skuse) (Diptera: Culicidae) under laboratory conditions. Through gas chromatography-mass spectrometry (GC-MS) analyses, we found that in sweet orange, mandarin, and lemon EOs, limonene was the most abundant compound, whereas linalyl acetate was the most abundant in the bergamot EO. All tested EOs showed a marked larvicidal activity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 44 publications
1
14
0
2
Order By: Relevance
“…The route of exposure, the environmental conditions and the physiological status of the target organism can affect the toxicity of botanicals 1921 . These substances have then been tested against a large number of arthropod pests, such as ingestion larvicides 22 , contacticides 23 , fumigants 24 , repellents 25,26 and antifeedants 27 . Among the various extracts, plant essential oils (EOs) have shown a good potential in controlling insect pests, as well as managing bacterial and fungal plant pathogens 2830 .…”
Section: Introductionmentioning
confidence: 99%
“…The route of exposure, the environmental conditions and the physiological status of the target organism can affect the toxicity of botanicals 1921 . These substances have then been tested against a large number of arthropod pests, such as ingestion larvicides 22 , contacticides 23 , fumigants 24 , repellents 25,26 and antifeedants 27 . Among the various extracts, plant essential oils (EOs) have shown a good potential in controlling insect pests, as well as managing bacterial and fungal plant pathogens 2830 .…”
Section: Introductionmentioning
confidence: 99%
“…EOs are constituted by a blend of 20 to 70 organic compounds, some of which represent more than 80% of the constituents as append, e.g., in Sweet Orange EO, the main compound, limonene reaches 88-97% of the whole oil [11,12]. Generally, the main components characterize the biological activity of the EOs.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, the results of our study confirm the larvicidal and insecticidal activity of limonene of C. limon essential oil against the genus Aedes. The study carried out by Campolo et al 44 showed the activity of this oil against Aedes albopictus larvae with a lethal concentration (LC50) of 145.27 mg L -1 after 24h exposure. However, the study of larvae, pulps and adults of Aedes albopictus 45 confirmed the activity of the oil with a lethal concentration (LC50) of 35.99 and 34.89 mg•L -1 for the enantiometric forms of limonene, respectively, R -(+) -limonene and S -(-)limonene.…”
Section: Discussionmentioning
confidence: 99%
“…Eclética Química Journal, vol. 44 limonene is the major component of oils from lemon peel (Citrus limon) and orange peel and of the essential oil of Carum carvi, being responsible for the prevention of dehydration and inhibition of microbial growth 4 .…”
Section: Introductionmentioning
confidence: 99%